The Propagation Effects of Lightning Electromagnetic Fields Over Mountainous Terrain in the Earth‐Ionosphere Waveguide. Issue 24 (26th December 2019) - Li, Dongshuai; Luque, Alejandro; Rachidi, Farhad; Rubinstein, Marcos; Azadifar, Mohammad; Diendorfer, Gerhard; Pichler, Hannes
Abstract: In this paper, a full‐wave two‐dimensional Finite‐Difference‐Time‐Domain model is developed to evaluate the propagation effects of lightning electromagnetic fields over mountainous terrain in the Earth‐ionosphere waveguide. In the model, we investigate the effect of the Earth‐ionosphere waveguide structure and medium parameters, including the effect of the ionospheric cold plasma characteristics, the effect of the Earth curvature, and the propagation effects over mountainous terrain. For the first time, the obtained results are validated against simultaneous experimental data consisting of lightning currents measured at the Säntis Tower and electric fields measured in Neudorf, Austria, located at 380‐km distance from the tower. It is shown that both the time delays and amplitudes of the lightning electromagnetic fields at 380‐km distance can be strongly affected by the ionospheric electron density profile, the mountainous terrain, and the Earth curvature. After taking into account the effect of the irregular terrain between the Säntis Tower and the field measurement station, the vertical electric fields calculated by using our model are found to be in good agreement with the corresponding measured cases occurred in both daytime and nighttime. The ideal approximation used in either the classical solutions or the simplified models might lead to inaccuracies in the estimated reflection height. Furthermore, we discuss the sensitivity of our results by considering different return stroke models, as well as different typical values of the return stroke speed and of the ground conductivity. Key Points: A new model is developed to analyze the effect of the medium parameters in the Earth‐ionosphere waveguide and tested with measured data The time delays and amplitudes of the fields are affected by the electron density profile, the earth curvature and mountainous terrain The numerical simulations agree well with the observations after taking into account the effect of the medium parameters in the ionosphere